Breeding report of a new Chinese cherry cultivar Shuguimei - WANG Yan; WANG Hao; ZHANG Jing; MA Yan; LIU Zhenshan; HE Wen; WU Zhiwei; FU Xiaoke; CHEN Qing; WANG Xiaorong (Guoshu xuebao, 2025)
Shuguimei is a new early-ripening Chinese cherry [Cerasus pseudocerasus (Lindl.) G. Don] cultivar bred by Sichuan Agricultural University. The cultivar was derived from a cross between Hongfei and Nanzaohong in 2016. Through artificial cross pollination, approximately 200 hybrid seedlings flowered in 2019. The hybrid seedling HN880 was initially selected as an excellent individual in 2020 for its superior performance and high quality. The field trials were conducted at three sites in Sichuan Province (including Chengdu city, Suining city and Xichang city) from 2020 to 2023. It was approved as a new Chinese cherry cultivar by the Sichuan Provincial Non-major Crop Cultivar Certification Committee in January 2025, and named as Shuguimei. The young trees exhibit vigorous growth with a semiopen posture. The branchlets are grayish-brown, and the mature leaves are green and oblong-ovate with a long tail tip and a round base. The inflorescence typically consists of corymbs with 3-6 flowers. The flower buds are reddish, and the petals are white with a pink margin. Each flower has five round petals, one pistil, and 35-45 stamens with orange-yellow anthers. The fruit is primarily elliptical, with orangered peel. Its flesh is light yellow, juicy, and rich in flavor. Fruit mass ranges from 4.5 to 5.6 g. The average longitudinal diameter is 1.95 cm, the transverse diameter 2.11 cm, with a fruit shape index around 0.93. The average pit mass is 0.29 g. The fruit stalk is medium in length, averaging 2.33 cm. The total soluble solid (TSS) content ranges from 14.5% to 16.9%, and the titratable acid (TA) content is about 0.42%, giving a TSS/TA ratio of about 37.33. Glucose and fructose are the main components of soluble sugars, with contents of 392.48 and 301.67 g·kg-1, respectively. Malic acid is the predominant organic acid, at 84.59 g·kg-1. The overall eating quality is excellent. In Chengdu, Sichuan Province, the fruit development period lasts about 48-52 days, maturing in early to mid-April, which is 5-7 days earlier than its male parent, Hongfei. The vegetative growth period is about 310 days. Shuguimei bears fruit earlier and has good yield potential, with a small yield in the second year after planting and substantial fruiting in the fourth to fifth year. The average yield can reach 8400-8700 kg·hm-2. Young trees bear more fruit on middle and long branches, while adult trees predominantly bear fruit on boundary branches, short branches, and medium to long branches. The cultivar shows strong growth potential, adaptability, and resistance to diseases. It is suitable for planting in areas with ecological conditions similar to those found in the plains and hills of Sichuan Province. Shuguimei is best suited for planting in sandy loam with good drainage and deep soil layers. Spacing recommended is (2.5-3) m × (3.5-4) m. It is suitable to adopt open-center or central leader system.